Does the Obligation to Obtain the Consent of a Third Party Extend to Taking Further Steps After Rejection? - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2015)
The question posed in the Court of Appeal case of The One Suites Pte Ltd v Pacific Motor Credit (Pte) Ltd [2015] SGCA 21 (“The One Suites”) was whether an obligation to use all reasonable endeavours to obtain the consent of a third party extends to taking further steps after the third party had refused to give such consent. To this, the Court, with Andrew Phang Boon Leong JA writing its grounds of decision, answered, “it depends but largely no”. More precisely, the Court said that while there almost invariably will be an implied obligation to use all reasonable endeavours to obtain the consent of a third party, it is less likely that such an obligation extends beyond rejection, particularly so when there is an express term providing that the contract is at an end following such rejection. In reaching this conclusion, the Court also discussed aspects of implied terms, as well as the doctrine of good faith in contract.